Finite element analysis and structural optimization design of multifunctional robotic arm for garbage truck - Li, Hainan; Li, Yang (Frontiers in Mechanical Engineering, 2025)
IntroductionWith the increasing demand for garbage disposal, complex operating environments and frequent use require garbage truck manipulators to have better performance.MethodsThis study designs a multifunctional robotic arm for garbage trucks, which has three basic degrees of freedom, is driven by hydraulic cylinders, and has a claw type end effector. Through the theory of relative motion of linkage mechanisms, the motion mechanics, including forward and inverse kinematics problems, are analyzed, and methods for calculating joint driving forces, rod angular velocities, and other parameters are determined. In structural optimization design, reducing the weight of the robotic arm is taken as the objective function. At the same time, considering performance indicators such as stiffness and strength, material selection, manufacturing errors, and cost constraints are set as constraints, and optimization is carried out using methods such as finite element analysis and topology optimization.ResultsAfter structural optimization, the overall mass of the objective function reached 64.39 kg after the 11th optimization, a decrease of about 14.28% compared to the initial 75.12 kg. In terms of manufacturing and processing factors, the optimized processing accuracy has been improved to ±0.15 mm, the cutting speed of some materials has been increased by about 20%, and the mold production cycle has been shortened by about 30%.DiscussionThe results show that the stress distribution of the optimized structure has changed but still meets the requirements of strength and stiffness. This optimized design effectively improves the performance of the robotic arm, reduces costs, and is beneficial for more stable and efficient operations in garbage collection and transportation.